2020
DOI: 10.1002/celc.202000544
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium‐Substituted Tungstosulfate Polyoxometalates as Peroxidase Mimetics and Their Potential Application in Biosensing

Abstract: This article reports on the peroxidase-like catalytic activity of polyoxometalates (POMs) and their potential use as natural peroxidases for developing a simple and efficient colorimetric glucose sensor. Two Keggin-type vanadium-substituted tungstosulfates, [SVW 11 O 40 ] 3À (SVW 11) and [SV 2 W 10 O 40 ] 4À (SV 2 W 10), were tested for their potential as natural enzyme mimetics and exhibited strong peroxidase-like catalytic activity. The catalysis reaction was found to be in accordance with Michaelis-Menten a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
(121 reference statements)
1
8
0
Order By: Relevance
“…The kinetics parameters for the samples prepared without GOx (PTA@MS-6.5/4.5 and PMA@MS-6.5/4.5) were further evaluated using H 2 O 2 as the substrate (Figure S14 and Table S4). The K m values of the samples taking H 2 O 2 as the substrate were much higher than those using oPD, signifying the requirement of higher concentrations of H 2 O 2 to achieve the maximum activity, as reported with other nanozyme systems earlier . Notably, the V max of PTA@MS-4.5 was ∼2 times higher than PTA@MS-6.5, whereas k cat remained nearly the same.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The kinetics parameters for the samples prepared without GOx (PTA@MS-6.5/4.5 and PMA@MS-6.5/4.5) were further evaluated using H 2 O 2 as the substrate (Figure S14 and Table S4). The K m values of the samples taking H 2 O 2 as the substrate were much higher than those using oPD, signifying the requirement of higher concentrations of H 2 O 2 to achieve the maximum activity, as reported with other nanozyme systems earlier . Notably, the V max of PTA@MS-4.5 was ∼2 times higher than PTA@MS-6.5, whereas k cat remained nearly the same.…”
Section: Resultssupporting
confidence: 57%
“…The K m values of the samples taking H 2 O 2 as the substrate were much higher than those using oPD, signifying the requirement of higher concentrations of H 2 O 2 to achieve the maximum activity, as reported with other nanozyme systems earlier. 50 Notably, the V max of PTA@MS-4.5 was ∼2 times higher than PTA@MS-6.5, whereas k cat remained nearly the same. Nevertheless, the data clearly indicated the fact that in the enzyme-nanozyme system (GOx-PTA/PMA@MS-6.5/ 4.5), the diffusion limitations played a role, whereas in the case of only nanozyme (PTA/PMA@MS-6.5/4.5), accessi-…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Understanding the redox activity of POMs toward proteins is of crucial importance since different studies have suggested that the redox properties of POMs are responsible for their antibacterial and antitumor activity. , For example, the observed reduction of K 6 [P 2 W 18 O 62 ]·14H 2 O and K 4 [SiMo 12 O 40 ]·3H 2 O in Gram-positive drug-resistant bacteria is an indication of their ability to penetrate through the cell wall and interfere with the electron transfer system of the cell, making these POMs effective antibacterial agents . Furthermore, the ability of POMs to oxidize biological substrates through activating H 2 O 2 , which is akin to the reactivity of peroxidase enzymes, has enabled their development as biosensors for the detection of H 2 O 2 – such as in colorimetric immunoassays for cancer cells–and as catalysts for the degradation of dye pollutants in water. , Therefore, the multiple emerging biological and medical applications of POMs incite studying the redox chemistry of POMs toward biomolecules. ,, …”
Section: Redox Activitymentioning
confidence: 99%
“…However, these peroxidase mimic systems with drawbacks such as long reaction time or high detection limit, prompt the search for novel efficient peroxidase mimetics. [59,60] Due to the abundant redox properties, POMs have been proven to catalyze the epoxidation of H 2 O 2 and the oxidation of organic substrates by O 2 or H 2 O 2 through a multistep electron transfer process. [61][62][63] For example, Mann et al recently exploited polymer/nucleotide coacervate microdroplets to reconfigure into membrane-bounded polyoxometalate coacervate vesicles (PCVs) in the presence of a bio-inspired Ru-based polyoxometalate catalyst and thus produce synzyme protocells (Ru 4 PCVs) with catalase-like activity (Figure 1A,B).…”
Section: Peroxidase Mimeticsmentioning
confidence: 99%